2018
DOI: 10.1148/radiol.2018173057
|View full text |Cite
|
Sign up to set email alerts
|

Brain Irradiation and Gadobutrol Administration in Pediatric Patients with Brain Tumors: Effect on MRI Brain Signal Intensity

Abstract: Purpose To determine whether treatment affects MRI signal intensity in pediatric patients with primary brain tumors independent of the administration of macrocyclic gadolinium-based contrast agents (GBCAs). Materials and Methods This retrospective, single-center study included 78 patients (mean age, 7.7 years ± 5.4) with primary brain tumors who underwent macrocyclic GBCA-enhanced MRI from 2015 to 2018. Three groups were compared: (a) patients who had undergone radiation therapy (37 patients, 26 of whom had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…SI changes in the DN in T 1 WI due to brain irradiation have been reported in previous studies . Kasahara et al were the first to exhibit an association between a history of radiation therapy to the brain and T 1 hyperintensity in the DN, but they did not consider the administration of GBCAs as a potential source of these changes.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…SI changes in the DN in T 1 WI due to brain irradiation have been reported in previous studies . Kasahara et al were the first to exhibit an association between a history of radiation therapy to the brain and T 1 hyperintensity in the DN, but they did not consider the administration of GBCAs as a potential source of these changes.…”
Section: Discussionmentioning
confidence: 82%
“…Tamrazi et al postulated that the SI changes described by Kasahara et al might be caused by gadolinium deposition. They also reported that brain irradiation affected the SI in T 1 WI within the DN independent of linear or macrocyclic GBCA administrations in pediatric patients with brain tumor. Additionally, they found there was no significant difference between a radiation therapy‐treated brain tumor group and the nontreated brain tumor group when the number of linear GBCA administrations was 11 to 20 in pediatric patients .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In several adult patient studies, statistical analysis revealed no significant effect of radiotherapy on SI changes in DN and GP [4, 5, 24]. It was also reported that MRI SI alterations in the DN has been found after radiotherapy independent of GBCA administration [25, 26].…”
Section: Introductionmentioning
confidence: 99%